Crime without punishment : aspects of the history of homicide - Friedman, Lawrence M., (Lawrence Meir), 1930- (Cambridge, United Kingdom : Cambridge University Press, 2018)
'In this compelling book, Lawrence M. Friedman looks at situations where killing is condemned by law but not by social norms and, therefore, is rarely punished. He shows how penal codes categorize homicides by degree of intent, which are in turn based on society's sense of moral outrage. Despite being officially defined as murder, many homicides have historically gone unpunished. Friedman looks at early vigilante justice, crimes of passion, murder of necessity, mercy killings, and assisted suicides. In his explorations of these unpunished homicides, Friedman probes what these circumstances tell us about conflicts in social and cultural norms and the interaction of law and society'--
Popular justice and injustice -- The unwritten law -- Dead on arrival -- The quality of mercy -- Black swans -- The meaning of unwritten law.
Includes bibliographical references and index.
Keywords: Homicide -- Law and legislation -- History -- United States; Homicide -- Social aspects -- United States